Archeologia totalitaryzmów —możliwości i perspektywy badawcze - Trzciński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Contemporary methods used by archeology create prospects for a fuller investigation of crimes against peace and humanity and of war crimes. Due to the lack of written sources or the limited scope of information that results from them, attempts can be made to find and interpret material sources directly related to the events under study. The methods used by archeologists can finally effectively verify information already obtained from archival sources. Today’s archeology extends its reach to the present, and new specializations such as archeology of armed conflicts or archeology of totalitarianisms contribute to a better identification of, among others, the contemporary history of Poland. These specializations are used all over the world in the process of investigating crimes against humanity and accompany ongoing criminal investigations.
Keywords: zbrodnie wojenne; ludobójstwo; archeologia totalitaryzmów